Implementation Of BPK Corporate University Policy At The State Financial Audit Education And Training Agency Of BPK RI - Anita Riknawati; Dahyar Daraba; Dyah Poespita Ernawati (Sean Institute, 2025)
BPK RI Establishes BPK Corporate University in 2021 as a strategy used to achieve BPK's vision and mission, by realizing a link and match between learning, knowledge management, and application of values ​​with BPK's performance targets. Therefore, the author is interested in taking the title